Metaphysical Anthropology of Conversation with the Dead: Naruto's Conversation with Minato In Konoha's Pain Attack - Salewa, Wandrio; Panuntun, Daniel Fajar (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2023)
Abstract: Fear and depression are ready to take control of a person's life if he hesitates to accept death. Similarly, Naruto experiences this in the Naruto shippuden series. When he was an infant, Naruto lost both of his parents. Surprisingly, Naruto met his father, Minato Namikaze, in Konoha while battling agony. The out-of-control Naruto almost took out the nine-tailed bijuu (kyubi), but his father prevented it, and Naruto regained the will and fortitude to battle Pain. Mark 5:35–42 and Daniel 12:1-3 will be used to support the method of metaphysical anthropology that will be employed. This paper examines the relationship between metaphysical anthropology in the Naruto shippuden and Mark 5:32–42 and Daniel 12:1–3 to construct a consolation concept to face grief. This study drew several conclusions, the first being that Christianity values life both before and after mortality, necessitating the development of contextual counseling techniques. Second, the conversation between Naruto and Minato during Pain's attack on Konoha has a noble value because it ultimately leads to Pain's revival and the restoration of Konoha. Thirdly, the Christian doctrine of the asleep soul in Mark 5:35–42 and Daniel 12:1-3, which rewards the soul after death, supports this research. Keywords: Death, Naruto, Metaphysical Anthropology, Soul